Sustainable Smart Cities A Vision for Tomorrow - Almusaed, Amjad; Almssad, Asaad (IntechOpen, 2023)
Rapid urbanization has led to many problems in cities, including climate change, deteriorating infrastructure, disorganized labor forces, and diminishing resources. This book presents a well-grounded vision for the kind of future city we need to live in by encapsulating the most salient and practical implementations of the many responsibilities and functions that characterize the modern metropolis. Furthermore, this book uses the idea of sustainability to show and analyze many theories and approaches to handling the topic of modern sustainable smart cities, as well as the effects they have on human life and the natural environment through sustainable development objectives and aims supported by the United Nations.